Pelatihan Bacaan Gharibul Qur’an Bagi Santri Pondok Pesantren Al-Kifayah Riau - Ningsih, Wirda; Hariati, Haryuni; Muhammad Fauzi, Irfan; Supri; Ihsan, Eri; Bahari, Zainul; Iqral, Muhammad (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2023)
The aim of the Gharibul Qur'an Reading Training at Al-Kifayah Riau Islamic Boarding School is to improve understanding and reading skills of the Qur'an, especially in various more complicated readings. The aim of this service is to give students a better understanding of the types of Gharibul Quran reading such as Tashil, Saktah, Imalah, Naql, Badal/Ibdal, and Isymam. To ensure good understanding, the training method involves discussions, practical approaches, and interactive sessions. Participants who took part in this training consisted of 35 students. The results of the service show that the level of student completion increased significantly after attending the training. In particular, the Naql reading type achieved the highest completeness, increasing from 55% to 95%. Other types of reading, such as Saktah, Imalah, and Badal/Ibdal, also experienced similar increases.